Journals for Computer-Mediated Learning: Publications of Value for the Online Educator - Matt Elbeck (Athabasca University Press, 2009)
In contrast with traditional academic disciplines, online educators do not have a generally accepted list of scholarly journals, which is in part a result of the multidisciplinary nature of the field, the relative infancy of online learning, and the view of online pedagogy as an instructional modality rather than a discrete academic discipline. The purpose of this study is to determine a comprehensive listing and relative value ranking of scholarly journals whose content informs online educators and motivates scholarship. After defining the scope of investigation to target peer-reviewed, scholarly journals with an explicit focus on computer-mediated learning (e.g., virtual, electronic, distance, distributive, mobile, and blended learning), 46 scholarly journals were identified as advancing the knowledge base in computer-mediated learning. Popularity, importance, prestige, and overall rankings for each journal are presented. The results inform online educators about the range of scholarly journals available and provide insight into the relative value of journals devoted to computer-mediated learning.